2020
DOI: 10.21891/jeseh.792984
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the views of biology teachers on distance education: The case study of COVID-19 Pandemic

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 26 publications
4
21
0
3
Order By: Relevance
“…When the results regarding the second subproblem of the study were examined, it was observed that the visual arts teachers mentioned experiencing problems related to internet access, lack of infrastructure, and learning process in the distance visual arts education process. Similar results were reported in previous studies that were conducted with teachers in other branches (Almanthari et al, 2020;Bakioğlu, Çevik, 2020;Bayburtlu, 2020;Karakaya et al, 2020;Sari and Nayır, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When the results regarding the second subproblem of the study were examined, it was observed that the visual arts teachers mentioned experiencing problems related to internet access, lack of infrastructure, and learning process in the distance visual arts education process. Similar results were reported in previous studies that were conducted with teachers in other branches (Almanthari et al, 2020;Bakioğlu, Çevik, 2020;Bayburtlu, 2020;Karakaya et al, 2020;Sari and Nayır, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…When the results obtained within the framework of the third subproblem of the study were examined, it was determined that the visual arts teachers preferred the direct instruction method more frequently in the distance visual arts education process compared to other methods and techniques. Similar results were reported in studies that were conducted with biology and science teachers (Bakioğlu, Çevik, 2020;Karakaya et al, 2020). According to the results obtained, it is suggested that novel plans and education programs should be regulated to prepare students and teachers for distance education in extraordinary disaster situations such as the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 82%
“…According to the results of the implemented SLR, no similar experiments have been reported to validate this implication. Likewise, the present investigation conceptually links the categories shown in Table A1, which are regularly studied non-simultaneously, as shown in the references [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Therefore, we consider that this work has an added value to the understanding of the teaching intervention phenomena that have taken place in post-COVID distance education.…”
Section: Discussionmentioning
confidence: 78%
“…Access to the internet at a fast speed and the availability of ICT devices seems to be a basic prerequisite for e-learning (Karakaya et al, 2020). However, the study showed that not all learners have a fast internet connection or a powerful electronic device.…”
Section: Discussionmentioning
confidence: 99%